2022
DOI: 10.3390/met12040684
|View full text |Cite
|
Sign up to set email alerts
|

Oxide Free Wire Arc Sprayed Coatings—An Avenue to Enhanced Adhesive Tensile Strength

Abstract: Conventionally, thermal spraying processes are almost exclusively carried out in an air atmosphere. This results in oxidation of the particles upon thermal spraying, and thus, the interfaces of the splats within the coating are oxidized as well. Hence, a full material bond strength cannot be established. To overcome this issue, a mixture of monosilane and nitrogen was employed in the present study as the atomising and environment gas. With this approach, an oxygen partial pressure corresponding to an extreme-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
(42 reference statements)
1
9
0
Order By: Relevance
“…The results of the oxygen measurement show that XHV-adequate oxygen concentrations can locally be achieved by adding silane to the arc process zone. This is similar to earlier results in related work [ 23 , 24 ]. The spectroscopic analyses are suitable to further elaborate the mechanisms leading to the previously found oxygen reduction.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of the oxygen measurement show that XHV-adequate oxygen concentrations can locally be achieved by adding silane to the arc process zone. This is similar to earlier results in related work [ 23 , 24 ]. The spectroscopic analyses are suitable to further elaborate the mechanisms leading to the previously found oxygen reduction.…”
Section: Discussionsupporting
confidence: 93%
“…Still, the thermodynamical consideration indicates that adding silane into a thermal plasma could theoretically reduce the thickness of an aluminum oxide layer. Prior studies already showed that very low oxygen contents in a process atmosphere could be achieved using silane [ 23 , 24 ]. If the oxide layer is removed by an ns-pulsed laser, a silane-doped atmosphere can prevent re-oxidation [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our experiments, the used oxygen sensor is a lambda probe known from exhaust gas analysis in combustion engines (Mesa GmbH, Germany) and suitable for trace oxygen measurements as previously shown in the literature. , The used lambda probe is based on a heated solid zirconia ceramic electrolyte ( T = 873 K) covered by a porous platinum layer, and a porous ceramic layer for the analyte site, respectively. The working principle is described in detail elsewhere. , According to the Nernst equation (eq ), the oxygen partial pressure of the analyte normalp normalO 2 normala normaln normala normall normaly normalt normale can be expressed by a reference pressure ( normalp normalO 2 normalr normale normalf normale normalr normale normaln normalc normale ), the Faraday constant F , the product of the universal gas constant and temperature RT , and the measured cell voltage U λ .…”
Section: Methodsmentioning
confidence: 99%
“…In our experiments, the used oxygen sensor is a lambda probe known from exhaust gas analysis in combustion engines (Mesa GmbH, Germany) and suitable for trace oxygen measurements as previously shown in the literature. 37,38 The used lambda probe is based on a heated solid zirconia ceramic electrolyte (T = 873 K) covered by a porous platinum layer, and a porous ceramic layer for the analyte site, respectively. The working principle is described in detail elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…[ 53 ] Additionally, a corundum blasting system was integrated into the chamber to enable a substrate surface preparation in the different atmospheres prior to the coating process. [ 54 ] Commercially pure copper (>99.8 wt% Cu) was sprayed on steel discs (steel grade S235JR, 1.0038). An overview showing the coating morphology obtained with spraying processes carried out in air (with air as atomizer gas) and in oxygen‐free atmosphere (with silane in nitrogen as atomizer gas) is depicted in Figure .…”
Section: Oxygen‐free Production Processesmentioning
confidence: 99%